A Newborn with Genital Ambiguity, 45,X/46,XY Mosaicism, a Jumping Chromosome Y, and Congenital Adrenal Hyperplasia - Lei Zhang; Linda D. Cooley; Sonal R. Chandratre; Atif Ahmed; Jill D. Jacobson (Case Reports in Endocrinology)
Disorders of sex development (DSD), formerly termed “intersex” conditions, arise from numerous causes. CAH secondary to 21-hydroxylase deficiency is the most common cause of DSD. Sex chromosome disorders, including sex chromosome mosaicism, are the second most common cause of DSD. We discuss a medically complex neonate with DSD presenting with ambiguous genitalia. Hormone levels suggested 21-hydroxylase deficiency. Molecular analysis revealed compound heterozygous mutations in the 21-hydroxylase gene (CYP21A2), confirming the diagnosis of CAH. Chromosome analysis revealed sex chromosome mosaicism with three cell lines: 45,X[8]/45,X,tas(Y;16)(p11.32;p13.3)[8]/45,X,t(Y;8)(p11.32;p23.3)[4] with the Y chromosome in telomere association with chromosomes 8p and 16p in different cell lines, a “jumping translocation.” Histologically, the right gonad had irregular, distended seminiferous tubules with hyperplastic germ cells contiguous with ovarian stroma and primordial follicles. The left gonad had scant ovarian stroma and embryonic remnants. Chromosome analyses showed mosaicism in both gonads: 45,X[17]/45,X,tas(Y;8)(p11.32;p23.3)[3]. This is the first case of coexisting CAH and 45,X/46,XY mosaicism reported in the English literature and the third case of a constitutional chromosome Y “jumping translocation.” Our report documents the medical and genetic complexity of children such as this one with ambiguous genitalia and discusses the need for a multidisciplinary team approach.